(untitled) (Economic studies journal, 2018)
In this paper we examined the link between hierarchical culture type and the frequency of administrative innovation in higher education institutions in Libya. Although much has been written about the link between organizational culture type and the frequency of innovation, no previous studies has been undertaken in the North Africa region, particularly in Libya. The main value of this paper is its analysis and testing of the relation of hierarchical culture and administration innovation. In addition, this topic has not been studied in depth and requires attention to hierarchical culture and administration innovation. The study used Organizational Innovation Assessment Instrument, and the Organizational Culture Assessment Instrument. Using Pearson correlation allowed us to explore the linkage between the independent variable and the dependent variable in public universities in Libya. In the study, hierarchical culture was hypothesized to have a positive correlation with frequency of administrative innovation. To test this hypothesis, data were gathered from 780 employees of higher education institutions in Libya. Respondents for the study included senior executives, administrators, and faculty members at Tripoli university, Benghazi university, Sirte university, Misurata university, Al Jabal Al Gharbi University and Sabha university. The researchers employed a quantitative method to determine the link between hierarchical culture and administrative innovation within the public Libyan universities. The findings indicate that the hierarchical culture type was statistically significantly related to administrative innovation. Specifically, a low positive correlation was found between hierarchical culture type and the frequency of administrative innovation.